Exploring ethical dilemmas in art therapy : 50 clinicians from 20 countries share their stories - Di Maria, Audrey Evans (New York, NY : Routledge, 2019)
Exploring Ethical Dilemmas in Art Therapy: 50 Clinicians From 20 Countries Share Their Stories presents a global collection of first-person accounts detailing the ethical issues that arise during art therapists' work. Grouped according to themes such as discrimination and inclusion, confidentiality, and scope of practice, chapters by experienced art therapists from 20 different countries explore difficult situations across a variety of practitioner roles, client diagnoses, and cultural contexts. In reflecting upon their own courses of action when faced with these issues, the authors acknowledge missteps as well as successes, allowing readers to learn from their mistakes. Offering a unique presentation centered on diverse vignettes with important lessons and ethical takeaways highlighted throughout, this exciting new volume will be an invaluable resource to all future and current art therapists, as well as to other mental health professionals.
From the Perspective of a Trainer: Is it Ethical to Train Others in Art Therapy Techniques?From the Perspective of a Professor: How to Support Students and Clients While Remaining Culturally Sensitive; Conclusion: Broadening Awareness, Boundaries, and Biases-Oh My!; References; 6 Culturally Adaptive Art Therapy Practice: Is it Ethical?; Concluding Thoughts; 7 Do No More.Harm: The Ethical Practice of Art Therapy with Hospitalized Adults Who Have Severe and Persistent Mental Illness; A Changing Context; Ethical Values; Boundaries; Autonomy; Beneficence; Fidelity; Justice; When Values Collide
OCLC-licensed vendor bibliographic record.
Keywords: Art therapy; Art therapy -- Moral and ethical aspects; Art therapists -- Professional ethics; HEALTH & FITNESS / Diseases / General; MEDICAL / Clinical Medicine; MEDICAL / Diseases; MEDICAL / Evidence-Based Medicine; MEDICAL / Internal Medicine; MEDICAL / Psychiatry / General; PSYCHOLOGY / Education & Training; PSYCHOLOGY / Reference